(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Digital therapeutics (DTx) are defined as software intended to treat or alleviate a disease, disorder, or condition. DTx may be conceptualised as technologies based on cognitive behavioural therapy techniques, which are capable of influencing patients’ behaviours. At present, there is a lack of clarity regarding the applicable legal framework for DTx, with only a limited number of solutions having been granted market authorisation. This paper investigates key legal issues regarding the regulation of DTx. First it is necessary to ascertain whether the regulations pertaining to medical devices are applicable. Other relevant issues include whether DTx could be prescribed by a medical practitioner, whether there should be a reimbursement from the national or local health service, as is in the case with pharmaceuticals, and who is liable for damage resulting from by malfunction or misuse of a defective instrument. The analysis employs comparative law methodologies and considers the following legal frameworks: the United States, the United Kingdom, the European Union, Germany, France, Belgium, and Italy.